Reinventing Modernity in Latin America Intellectuals Imagine the Future, 1900-1930 - Miller, N.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This is an exploration of how Latin America developed an alternative modernity during the early twentieth century, one that challenges the key assumptions of the Western dominant model.
Keywords: Ethnology—Latin America; America—History.; Civilization—History.; Latin America—Politics and government; Social history; World politics; Latin American Culture; History of the Americas; Cultural History; Latin American Politics; Social History; Political History